Advancing European paediatric research - the contribution of the Innovative Health Initiative - Seigneuret, Nathalie (Frontiers in Medicine, 2025)
Children deserve health solutions, including medicines, medical devices and diagnostics, that are adapted to their needs. They should not be left behind when it comes to benefitting from innovations. The introduction of paediatric legislation in the EU and US in the 2000s dramatically changed the regulatory environment by fostering the development of medicines for children. However, the development of paediatric medicines remains challenging, and many needs remain unmet. When it comes to medical devices and in vitro diagnostics (IVDs), very few are designed and intended specifically for use in children, leading doctors to use adult devices and adapt them to fit children. To address the scientific, technical, and operational challenges related to paediatric development, multi-stakeholder collaboration is key. The European public-private partnerships the Innovative Health Initiative (IHI), and its predecessor the Innovative Medicines Initiative (IMI), contribute to advancing paediatric research by bringing together the private health industry sectors and public partners including academia, healthcare providers, patients and carers, regulators, and health technology assessment bodies. Several of their large collaborative research projects have already produced significant results that are optimising the development of paediatric medicines. This article looks at these achievements and discusses opportunities for further public-private collaborative research to boost the development of innovative health solutions that address specifically all children’s needs.